Monitoring Leishmania infection and exposure to Phlebotomus perniciosus using minimal and non-invasive canine samples - Maia, Carla (2021)
BACKGROUND: In endemic areas of zoonotic leishmaniosis caused by L. infantum, early detection of Leishmania infection in dogs is essential to control the dissemination of the parasite to humans. The aim of this study was to evaluate the serological and/or molecular diagnostic performance of minimally and non-invasive samples (conjunctiva cells (CS) and peripheral blood (PB)) for monitoring Leishmania infection/exposure to Phlebotomus perniciosus salivary antigens in dogs at the beginning and the end of sand fly seasonal activity (May and October, respectively) and to assess associated risks factors. METHODS: A total of 208 sheltered dogs from endemic areas of leishmaniosis were screened. Leishmania DNA detection in PB on filter paper and CS was performed by nested-PCR (nPCR), while the detection of anti-Leishmania antibodies was performed using IFAT and ELISA. The exposure to P. perniciosus salivary antigens (SGH, rSP01 and rSP03B + rSP01) was measured by ELISA. RESULTS: Ninety-seven (46.6%) and 116 (55.8%) of the 208 dogs were positive to Leishmania antibodies or DNA by at least one test at the beginning and end of the sand fly season, respectively. IFAT and ELISA presented a substantial agreement in the serodiagnosis of leishmaniosis. Discrepant PB nPCR results were obtained between sampling points. Leishmania DNA was detected in CS of 72 dogs at the end of the phlebotomine season. The presence of antibodies to the parasite measured by ELISA was significantly higher in dogs presenting clinical signs compatible with leishmaniosis at both sampling points. Phlebotomus perniciosus salivary antibodies were detected in 179 (86.1%) and 198 (95.2%) of the screened dogs at the beginning and end of the phlebotomine season, respectively. CONCLUSIONS: The association between ELISA positivity and clinical signs suggests its usefulness to confirm a clinical suspicion. CS nPCR seems to be an effective and non-invasive method for assessing early exposure to the parasite. PB nPCR should not be used as the sole diagnostic tool to monitor Leishmania infection. The correlation between the levels of antibodies to P. perniciosus saliva and Leishmania antibodies suggests the use of a humoral response to sand fly salivary antigens as biomarkers of L. infantum infection.